Super-heat-shock self-adhesive transposed conductor and preparation method thereof

CN122930656APending Publication Date: 2026-10-16沈阳昌盛电气设备科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228769.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有技术很难优化产品的耐热冲击、绝缘以及自粘层的粘结强度性能,同时产品耐候、耐不同程度的腐蚀稳定性差,产品的综合协调性差,进一步的限制了产品的使用效率

Benefits of technology

本发明自粘换位导线采用铜扁线导体经过清洗、干燥,再配合改性绝缘底漆进行烘焙固化,再通过配合自粘改性漆、绝缘纸进行联合改进处理,得到的自粘换位导线耐热冲击、绝缘以及自粘层的粘结强度性能优异,同时产品耐候、耐不同程度的腐蚀稳定性效果显著,产品的综合协调性优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of transposed conductor, in particular to super heat shock resistance self-adhesive transposed conductor and its preparation method, comprising the following steps: arranging copper flat wire into two columns with wide surfaces contacting each other, transposing the two columns of self-adhesive enameled flat wire on the upper and lower surfaces along the narrow surface in the same direction to obtain transposed conductor core; then wrapping the transposed conductor core with 5-7 layers of continuous and compact insulation paper to obtain super heat shock resistance self-adhesive transposed conductor. The self-adhesive transposed conductor of the present application uses copper flat wire conductor which is cleaned and dried, then baked and solidified with modified insulation primer, and then improved and treated with self-adhesive modified paint and insulation paper, so that the obtained self-adhesive transposed conductor has excellent heat shock resistance, insulation and bonding strength performance of the self-adhesive layer, and has excellent weather resistance, corrosion resistance stability and comprehensive coordination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of transposition conductor technology, specifically to ultra-thermal shock resistant self-adhesive transposition conductors and their preparation methods. Background Technology

[0002] Transposed conductors are conductors composed of two rows of enameled copper flat wires in contact with each other on the wide side, which are transposed in the same direction on the top and bottom sides of the two rows of enameled wires as required, and then wrapped with multiple layers of electrical insulating paper tape. Transposed conductors are widely used in the winding coils of large power transformers, reactors and special transformers.

[0003] Existing technologies make it difficult to optimize the product's thermal shock resistance, insulation, and self-adhesive layer bonding strength. At the same time, the product has poor weather resistance and resistance to varying degrees of corrosion, and its overall coordination is poor, further limiting the product's efficiency. Summary of the Invention

[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide an ultra-heat-shock resistant self-adhesive transposition conductor and its preparation method, so as to solve the problems mentioned in the background art.

[0005] The present invention solves the technical problem by adopting the following technical solution: This invention provides a method for preparing ultra-thermal shock resistant self-adhesive transposition conductors, comprising the following steps: Step 1: Clean and dry the copper flat wire conductor, then coat it with a modified insulating primer, and then bake and cure it to obtain a primer layer with a thickness of 0.1~0.12mm; Step two, then apply a self-adhesive modified paint to the outside of the primer layer, and then cure to form a self-adhesive layer with a thickness of 0.04~0.06mm; Step 3: Arrange 19 to 37 copper flat wires made in Step 2 into two columns with their wide sides in contact with each other. Then, transpose the two columns of self-adhesive enameled flat wires in the same direction along their narrow sides to obtain transposed wire cores. Step four: Wrap the transposed core with 5 to 7 layers of continuous and tight insulating paper to obtain an ultra-heat-shock resistant self-adhesive transposed conductor.

[0006] Preferably, the baking and curing in step one is carried out using a vertical enameling oven, with the inlet temperature of the vertical enameling oven controlled at 120~140℃, the lower section temperature at 220~250℃, the middle section temperature at 300~350℃, the upper section temperature at 350~400℃, and the oven speed at 8~12m / min. In step two, the curing process is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled as follows: inlet temperature 120~150℃, lower temperature 160~200℃, middle temperature 280~310℃, upper temperature 320~350℃, and oven speed 8~12m / min.

[0007] Preferably, the modified insulating primer is prepared by: S1, by weight, heat 100-110 parts of acetal resin to 100-105℃, keep warm, and set aside. Then add 8-12 parts of modified montmorillonite agent and 1-3 parts of silane coupling agent KH560 to 30-50 parts of ethanol solvent and mix thoroughly to obtain the additive. S2, add the additive to the prepared acetal resin and stir for 2-4 hours, then cool to 80-85℃, add 8-12 parts of curing agent, stir evenly to obtain modified insulating primer.

[0008] Preferably, the curing agent is a blocked isocyanate curing agent, and the blocked isocyanate curing agent is an imidazole blocked isocyanate.

[0009] Preferably, the modified montmorillonite agent is prepared by: S1a, montmorillonite is first stirred evenly in a sulfuric acid solution with a mass fraction of 5-8% at 10-15 times the total weight of montmorillonite, then washed with water, filtered, and dried to obtain dry montmorillonite; S1b: 5-8 parts by weight of montmorillonite are dispersed in 15-20 parts by weight of N,N-dimethylformamide, and 2-3 parts by weight of furanylmethyl glycidyl ether are added. The mixture is reacted at 60-65°C for 5-8 hours. After the reaction is completed, the mixture is washed with water, filtered, and dried to obtain furanylated montmorillonite. S1c, furanized montmorillonite and graphene modified liquid were stirred at a weight ratio of 3:(5~7) for 1~2 hours at a stirring speed of 450~550 r / min and a stirring temperature of 55~60℃. After stirring, the mixture was filtered and dried to obtain the modified montmorillonite agent.

[0010] Preferably, the graphene-modified liquid is prepared by: S1c1, mix 2-3 parts by weight of silane coupling agent KH550 and 30-35 parts by weight of 80-85% ethanol solution, then adjust the pH to 4.5-5.0 with acetic acid, then add 4-7 parts by weight of additive, and continue to stir evenly to obtain the modified solution. The preparation method of the additive is as follows: 2-4 parts by weight of α-silicon nitride, 1-3 parts by weight of aluminum borate whiskers, 5-8 parts by weight of 2-5% lanthanum chloride solution, and 2-3 parts by weight of zirconium oxide are blended and ball-milled thoroughly. After ball milling, the mixture is filtered and dried to obtain the additive. S1c2, graphene and the modified liquid are ultrasonically modified at a weight ratio of 5:(8~11), ultrasonic power 350~450W, ultrasonic for 1~2h, and after ultrasonication is completed, graphene modified liquid is obtained.

[0011] The modified insulating primer uses acetal resin as the matrix, combined with modified montmorillonite, silane coupling agent KH560 and other raw materials. The added modified montmorillonite is activated by sulfuric acid, modified by furan methyl glycidyl ether, and composite treated with graphene modified liquid. Its sheet structure forms interpenetrating reinforcement in the acetal resin, effectively hindering the propagation of cracks under high temperature bending stress. The graphene in the graphene modified liquid is uniformly dispersed in the resin matrix after being synergistically modified by multiple components such as α-silicon nitride, aluminum borate whiskers, lanthanum chloride and zirconium oxide, which significantly improves the crack resistance and heat aging resistance of the paint film. At the same time, through the synergistic effect of the sheet barrier of the modified montmorillonite and the two-dimensional barrier of the graphene modified liquid, a highly efficient anti-corrosion barrier is formed, and the overall performance of the product is coordinated and optimized.

[0012] Preferably, the preparation method of the self-adhesive modified paint is as follows: S11, by weight, 100-110 parts of bisphenol A type epoxy resin and 20-25 parts of phenolic epoxy resin are added to a reaction vessel, heated to 90-92℃ and stirred to dissolve, and then 10-15 parts of carboxyl-terminated liquid nitrile rubber are added, and reacted at 105-110℃ for 2-3 hours to obtain toughened modified epoxy resin. S12, then the toughened modified epoxy resin is cooled to 65~70℃, and 7~9 parts of dicyandiamide curing agent, 1~3 parts of 2-methylimidazole, 50~55 parts of mixed solvent and 5~8 parts of modified carbon nanotube agent are added and mixed evenly to obtain self-adhesive modified paint.

[0013] Preferably, the mixed solvent is prepared by mixing butanone and propylene glycol methyl ether acetate in a weight ratio of (1~2):1; the number average molecular weight of the terminal carboxyl liquid nitrile rubber is 3000~5000, and the carboxyl content is 0.05~0.10 mol / kg; the epoxy equivalent of the bisphenol A type epoxy resin is 180~200 g / eq; and the epoxy equivalent of the phenolic epoxy resin is 160~180 g / eq.

[0014] Preferably, the modified carbon nanotube agent is prepared by: S121, add carbon nanotubes to a mixed acid with a weight of 5 to 8 times the total weight of carbon nanotubes, reflux at 60 to 80°C for 2 to 4 hours, cool, dilute with deionized water, filter, wash with deionized water until pH is 6.5 to 7.0, and dry at 80 to 100°C for 12 to 24 hours to obtain purified carbon nanotubes. S122, 2-5 parts by weight of αAl2O3, 2-3 parts by weight of sheet-like boron nitride, 1-2 parts by weight of hollow glass microspheres, 8-12 parts by weight of 75-85% ethanol solution, and 1-2 parts by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:(5-7). Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123: 10-15 parts by weight of carbon nanotube composite are dispersed in 35-40 parts by weight of deionized water, 2-5 parts by weight of cobalt nitrate are added, the mixture is stirred at room temperature for 2-4 hours, filtered, dried at 80-85℃, and then heat-treated at 150-200℃ for 1-2 hours under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a weight ratio of (3~5):1.

[0015] The self-adhesive modified paint uses CTBN-toughened modified bisphenol A epoxy resin and is compounded with phenolic epoxy resin to improve crosslinking density and heat resistance. At the same time, modified carbon nanotube agents are introduced to coordinate and optimize the product's functional effects. The modified carbon nanotube agents are purified by acid and then reinforced by blending with αAl2O3 / flake boron nitride / hollow glass microspheres. Furthermore, the product is anchored and improved through cobalt nitrate heat treatment. Through the coordination and optimization of raw materials, the product's functionality is further improved.

[0016] The carbon nanotubes are multi-walled carbon nanotubes with an outer diameter of 10–30 nm, a length of 5–15 μm, and a specific surface area of ​​200–300 m². 2 / g; the plate-like boron nitride is hexagonal boron nitride with an average particle size (D50) of 1~5μm and a thickness of 50~200nm; the average particle size (D50) of α-silicon nitride is 0.5~2μm, and the α phase content is ≥92%; the diameter of the aluminum borate whiskers is 0.5~1.5μm, the length is 10~30μm, and the aspect ratio is 10~20:1; the zirconium oxide is nano-zirconia with an average particle size of 30~80nm; the montmorillonite is sodium-based montmorillonite with a particle size of 300-500 mesh; the graphene is graphene oxide with 1~3 layers, a sheet diameter (D50) of 1~10μm, and an oxygen content (C / O ratio) of 2:1~3:1.

[0017] This invention also provides a method for preparing a self-adhesive transposition conductor with ultra-thermal shock resistance.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The self-adhesive transposition conductor of this invention uses copper flat wire conductors that are cleaned, dried, and then baked and cured with modified insulating primer. It is further improved by combining it with self-adhesive modified paint and insulating paper. The resulting self-adhesive transposition conductor has excellent thermal shock resistance, insulation and self-adhesive layer bonding strength. At the same time, the product has significant weather resistance and corrosion stability of different degrees, and the overall product has excellent coordination. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1.

[0021] The method for preparing the ultra-thermal shock resistant self-adhesive transposition wire in this embodiment includes the following steps: Step 1: Clean and dry the copper flat wire conductor, then coat it with a modified insulating primer, and then bake and cure it to obtain a primer layer with a thickness of 0.1mm. Step two, then apply a self-adhesive modified paint to the outside of the primer layer, and then cure to form a self-adhesive layer with a thickness of 0.04mm; Step 3: Arrange the 19 copper flat wires made in Step 2 into two columns with their wide sides in contact with each other. Then, transpose the two columns of self-adhesive enameled flat wires in the same direction along their narrow sides to obtain transposed wire cores. Step four: Wrap the transposed core with five layers of insulating paper in a continuous and tight manner to obtain an ultra-heat-shock resistant self-adhesive transposed conductor.

[0022] The baking and curing process described in step one is carried out using a vertical enameling oven. The temperature of the inlet section of the vertical enameling oven is controlled at 120℃, the temperature of the lower section is 220℃, the temperature of the middle section is 300℃, the temperature of the upper section is 350℃, and the oven speed is 8m / min. In step two, the curing process is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled as follows: inlet temperature 120℃, lower temperature 160℃, middle temperature 280℃, upper temperature 320℃, and the oven speed is 8m / min.

[0023] The preparation method of the modified insulating primer in this embodiment is as follows: S1, by weight, heat 100 parts of acetal resin to 100℃, keep warm, and set aside. Then add 8 parts of modified montmorillonite agent and 1 part of silane coupling agent KH560 to 30 parts of ethanol solvent and mix thoroughly to obtain the additive. S2, add the additive to the prepared acetal resin and stir for 2 hours, then cool to 80°C, add 8 parts of curing agent, stir evenly, and obtain the modified insulating primer.

[0024] The curing agent is a blocked isocyanate curing agent, which is an imidazole blocked isocyanate.

[0025] The preparation method of the modified montmorillonite agent in this embodiment is as follows: S1a, montmorillonite is first stirred evenly in a 5% sulfuric acid solution with a mass fraction 10 times the total weight of montmorillonite, then washed with water, filtered, and dried to obtain dry montmorillonite; S1b, 5 parts by weight of montmorillonite were dispersed in 15 parts by weight of N,N-dimethylformamide, and 2 parts by weight of furanylmethyl glycidyl ether were added. The mixture was reacted at 60°C for 5 hours. After the reaction was completed, the mixture was washed with water, filtered, and dried to obtain furanyl montmorillonite. S1c, furanized montmorillonite, and graphene modified liquid were stirred at a weight ratio of 3:5, with a stirring speed of 450 r / min, for 1 h, and a stirring temperature of 55℃. After stirring, the mixture was filtered and dried to obtain the modified montmorillonite agent.

[0026] The preparation method of the graphene-modified liquid in this embodiment is as follows: S1c1, mix 2 parts by weight of silane coupling agent KH550 and 30 parts by weight of 80% ethanol solution, then adjust the pH value to 4.5 with acetic acid, then add 4 parts by weight of additive, and continue to stir evenly to obtain the modified solution. The preparation method of the additive is as follows: Two parts by weight of α-silicon nitride, one part by weight of aluminum borate whiskers, five parts by weight of 2-5% lanthanum chloride solution, and two parts by weight of zirconium oxide were blended and ball-milled thoroughly. After ball milling, the mixture was filtered and dried to obtain the additive. S1c2, graphene and modification liquid are ultrasonically modified at a weight ratio of 5:8, ultrasonic power 350W, ultrasonic for 1 hour, and after ultrasonication is completed, graphene modification liquid is obtained.

[0027] The preparation method of the self-adhesive modified paint in this embodiment is as follows: S11, by weight, 100 parts of bisphenol A type epoxy resin and 20 parts of phenolic epoxy resin are added to the reactor, heated to 90°C and stirred to dissolve, and then 10 parts of carboxyl-terminated liquid nitrile rubber are added. The mixture is reacted at 105°C for 2 hours to obtain toughened modified epoxy resin. S12, then the toughened modified epoxy resin is cooled to 65°C, and 7 parts of dicyandiamide curing agent, 1 part of 2-methylimidazole, 50 parts of mixed solvent and 5 parts of modified carbon nanotube agent are added and mixed evenly to obtain self-adhesive modified paint.

[0028] In this embodiment, the mixed solvent is prepared by mixing methyl ethyl ketone (MEK) and propylene glycol methyl ether acetate in a weight ratio of 1:1; the number average molecular weight of the terminal carboxyl liquid nitrile rubber is 3000, and the carboxyl content is 0.05 mol / kg; the epoxy equivalent of the bisphenol A type epoxy resin is 180 g / eq; and the epoxy equivalent of the phenolic epoxy resin is 160 g / eq.

[0029] The preparation method of the modified carbon nanotube agent in this embodiment is as follows: S121, carbon nanotubes were added to a mixed acid at 5 times the total weight of the carbon nanotubes, refluxed at 60°C for 2 hours, cooled, diluted with deionized water, filtered, washed with deionized water until the pH was 6.5, and dried at 80°C for 12 hours to obtain purified carbon nanotubes. S122, 2 parts by weight of αAl2O3, 2 parts by weight of sheet boron nitride, 1 part by weight of hollow glass microspheres, 8 parts by weight of 75% ethanol solution, and 1 part by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:5. Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123, 10 parts by weight of carbon nanotube composite were dispersed in 35 parts by weight of deionized water, 2 parts by weight of cobalt nitrate were added, stirred at room temperature for 2 hours, filtered and dried at 80°C, and then heat-treated at 150°C for 1 hour under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 3:1.

[0030] The self-adhesive transposition conductor prepared by the method described in this embodiment is a super heat shock resistant self-adhesive transposition conductor.

[0031] The carbon nanotubes in this embodiment are multi-walled carbon nanotubes with an outer diameter of 10 nm, a length of 5 μm, and a specific surface area of ​​200 m². 2 / g; the plate-like boron nitride is hexagonal boron nitride with an average particle size (D50) of 1μm and a thickness of 50nm; the average particle size (D50) of α-silicon nitride is 0.5μm, and the α phase content is ≥92%; the aluminum borate whiskers have a diameter of 0.5μm, a length of 10μm, and an aspect ratio of 10:1; the zirconium oxide is nano-zirconia with an average particle size of 30nm; the montmorillonite is sodium-based montmorillonite with a particle size of 300 mesh; the graphene is graphene oxide with 1 layer, a sheet diameter (D50) of 1μm, and an oxygen content (C / O ratio) of 2:1.

[0032] Example 2.

[0033] The method for preparing the ultra-thermal shock resistant self-adhesive transposition wire in this embodiment includes the following steps: Step 1: Clean and dry the copper flat wire conductor, then coat it with a modified insulating primer, and then bake and cure it to obtain a primer layer with a thickness of 0.12mm. Step two, then apply a self-adhesive modified paint to the outside of the primer layer, and then cure to form a self-adhesive layer with a thickness of 0.06mm; Step 3: Arrange the 37 copper flat wires made in Step 2 into two columns with their wide sides in contact with each other. Then, transpose the two columns of self-adhesive enameled flat wires in the same direction along their narrow sides to obtain transposed wire cores. Step four: Wrap the transposed core with 7 layers of continuous and tight insulating paper to obtain an ultra-heat-shock resistant self-adhesive transposed conductor.

[0034] The baking and curing process described in step one is carried out using a vertical enameling oven. The temperature of the inlet section of the vertical enameling oven is controlled at 140℃, the temperature of the lower section is 250℃, the temperature of the middle section is 350℃, the temperature of the upper section is 400℃, and the oven speed is 12m / min. In step two, the curing process is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled as follows: inlet temperature 150℃, lower temperature 200℃, middle temperature 310℃, upper temperature 350℃, and oven speed 12m / min.

[0035] The preparation method of the modified insulating primer in this embodiment is as follows: S1, by weight, heat 110 parts of acetal resin to 105℃, keep warm, and set aside. Then add 12 parts of modified montmorillonite agent and 3 parts of silane coupling agent KH560 to 50 parts of ethanol solvent and mix thoroughly to obtain the additive. S2, add the additive to the prepared acetal resin and stir for 4 hours, then cool to 85°C, add 12 parts of curing agent, stir evenly, and obtain the modified insulating primer.

[0036] Preferably, the curing agent is a blocked isocyanate curing agent, and the blocked isocyanate curing agent is an imidazole blocked isocyanate.

[0037] The preparation method of the modified montmorillonite agent in this embodiment is as follows: S1a, montmorillonite is first stirred evenly in a sulfuric acid solution with a mass fraction of 8% and a weight multiple of 15 times the total weight of montmorillonite, then washed with water, filtered, and dried to obtain dry montmorillonite; S1b, 8 parts by weight of montmorillonite were dispersed in 20 parts by weight of N,N-dimethylformamide, and 3 parts by weight of furanylmethyl glycidyl ether were added. The mixture was reacted at 65°C for 8 hours. After the reaction was completed, the mixture was washed with water, filtered, and dried to obtain furanylated montmorillonite. S1c, furanized montmorillonite, and graphene modified liquid were stirred at a weight ratio of 3:7, with a stirring speed of 550 r / min for 2 h and a stirring temperature of 60℃. After stirring, the mixture was filtered and dried to obtain the modified montmorillonite agent.

[0038] The preparation method of the graphene-modified liquid in this embodiment is as follows: S1c1, mix 3 parts by weight of silane coupling agent KH550 and 35 parts by weight of 85% ethanol solution, then adjust the pH to 5.0 with acetic acid, then add 7 parts by weight of additive, and continue to stir until uniform to obtain modified solution. The preparation method of the additive is as follows: Four parts by weight of α-silicon nitride, three parts by weight of aluminum borate whiskers, eight parts by weight of 5% lanthanum chloride solution, and three parts by weight of zirconium oxide were blended and ball-milled thoroughly. After ball milling, the mixture was filtered and dried to obtain the additive. S1c2, graphene and modification liquid are ultrasonically modified at a weight ratio of 5:11, ultrasonic power 450W, ultrasonic for 2 hours, and after ultrasonication is completed, graphene modification liquid is obtained.

[0039] The preparation method of the self-adhesive modified paint in this embodiment is as follows: S11, by weight, 110 parts of bisphenol A type epoxy resin and 25 parts of phenolic epoxy resin are added to a reaction vessel, heated to 92°C and stirred to dissolve, and then 15 parts of carboxyl-terminated liquid nitrile rubber are added. The reaction is carried out at 110°C for 3 hours to obtain toughened modified epoxy resin. S12, then the toughened modified epoxy resin is cooled to 70°C, and 9 parts of dicyandiamide curing agent, 3 parts of 2-methylimidazole, 55 parts of mixed solvent and 8 parts of modified carbon nanotube agent are added and mixed evenly to obtain self-adhesive modified paint.

[0040] In this embodiment, the mixed solvent is prepared by mixing methyl ethyl ketone (MEK) and propylene glycol methyl ether acetate in a weight ratio of 2:1; the number average molecular weight of the terminal carboxyl liquid nitrile rubber is 5000, and the carboxyl content is 0.10 mol / kg; the epoxy equivalent of the bisphenol A type epoxy resin is 200 g / eq; and the epoxy equivalent of the phenolic epoxy resin is 180 g / eq.

[0041] The preparation method of the modified carbon nanotube agent in this embodiment is as follows: S121, carbon nanotubes were added to a mixed acid with a weight of 8 times the total weight of carbon nanotubes, refluxed at 80°C for 4 hours, cooled, diluted with deionized water, filtered, washed with deionized water until pH 7.0, and dried at 100°C for 24 hours to obtain purified carbon nanotubes. S122, 5 parts by weight of αAl2O3, 3 parts by weight of sheet boron nitride, 2 parts by weight of hollow glass microspheres, 12 parts by weight of 85% ethanol solution, and 2 parts by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:7. Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123, 15 parts by weight of carbon nanotube composite were dispersed in 40 parts by weight of deionized water, 5 parts by weight of cobalt nitrate were added, stirred at room temperature for 4 hours, filtered and dried at 85°C, and then heat-treated at 200°C for 2 hours under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 5:1.

[0042] The self-adhesive transposition conductor prepared by the method described in this embodiment is a super heat shock resistant self-adhesive transposition conductor.

[0043] The carbon nanotubes in this embodiment are multi-walled carbon nanotubes with an outer diameter of 30 nm, a length of 15 μm, and a specific surface area of ​​300 m². 2 / g; the plate-like boron nitride is hexagonal boron nitride with an average particle size (D50) of 5μm and a thickness of 200nm; the α-silicon nitride has an average particle size (D50) of 2μm and an α phase content of ≥92%; the aluminum borate whiskers have a diameter of 1.5μm, a length of 30μm, and an aspect ratio of 20:1; the zirconium oxide is nano-zirconia with an average particle size of 80nm; the montmorillonite is sodium-based montmorillonite with a particle size of 500 mesh; the graphene is graphene oxide with 3 layers, a sheet diameter (D50) of 10μm, and an oxygen content (C / O ratio) of 3:1.

[0044] Example 3.

[0045] The method for preparing the ultra-thermal shock resistant self-adhesive transposition wire in this embodiment includes the following steps: Step 1: Clean and dry the copper flat wire conductor, then coat it with a modified insulating primer, and then bake and cure it to obtain a primer layer with a thickness of 0.11mm. Step two, then apply a self-adhesive modified paint to the outside of the primer layer, and then cure to form a self-adhesive layer with a thickness of 0.05mm; Step 3: Arrange the 31 copper flat wires made in Step 2 into two columns with their wide surfaces in contact with each other. Then, transpose the two columns of self-adhesive enameled flat wires in the same direction along their narrow surfaces to obtain transposed wire cores. Step four: Wrap the transposed core with six layers of continuous and tight insulating paper to obtain an ultra-heat-shock resistant self-adhesive transposed conductor.

[0046] The baking and curing process described in step one is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled at 130℃, the lower section temperature at 235℃, the middle section temperature at 325℃, and the upper section temperature at 375℃. The oven speed is 10m / min. In step two, the curing process is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled as follows: inlet temperature 135℃, lower temperature 180℃, middle temperature 290℃, upper temperature 320℃, and oven speed 10m / min.

[0047] The preparation method of the modified insulating primer in this embodiment is as follows: S1, by weight, heat 105 parts of acetal resin to 102℃, keep warm, and set aside. Then add 10 parts of modified montmorillonite agent and 2 parts of silane coupling agent KH560 to 45 parts of ethanol solvent and mix thoroughly to obtain the additive. S2, add the additive to the prepared acetal resin and stir for 3 hours, then cool to 82°C, add 10 parts of curing agent, stir evenly, and obtain the modified insulating primer.

[0048] The curing agent is a blocked isocyanate curing agent, which is an imidazole blocked isocyanate.

[0049] The preparation method of the modified montmorillonite agent in this embodiment is as follows: S1a, montmorillonite is first stirred evenly in a sulfuric acid solution with a mass fraction of 5-8% at 12.5 times the total weight of montmorillonite, then washed with water, filtered, and dried to obtain dry montmorillonite; S1b, 6.5 parts by weight of montmorillonite were dispersed in 17.5 parts by weight of N,N-dimethylformamide, and 2.5 parts by weight of furanylmethyl glycidyl ether were added. The mixture was reacted at 62°C for 6.5 h. After the reaction was completed, the mixture was washed with water, filtered, and dried to obtain furanylated montmorillonite. S1c, furanized montmorillonite, and graphene modified liquid were stirred at a weight ratio of 3:6, with a stirring speed of 500 r / min for 1.5 h and a stirring temperature of 57℃. After stirring, the mixture was filtered and dried to obtain the modified montmorillonite agent.

[0050] The preparation method of the graphene-modified liquid in this embodiment is as follows: S1c1, mix 2.5 parts by weight of silane coupling agent KH550 and 32.5 parts by weight of 82% ethanol solution, then adjust the pH to 4.7 with acetic acid, then add 5.5 parts by weight of additive, and continue to stir until uniform to obtain the modified solution. The preparation method of the additive is as follows: Three parts by weight of α-silicon nitride, two parts by weight of aluminum borate whiskers, 6.5 parts by weight of 3.5% lanthanum chloride solution, and 2.5 parts by weight of zirconium oxide were blended and ball-milled thoroughly. After ball milling, the mixture was filtered and dried to obtain the additive. S1c2, graphene and modifying liquid are ultrasonically modified at a weight ratio of 5:9, ultrasonic power 400W, ultrasonic for 1.5h, and after ultrasonication is completed, graphene modified liquid is obtained.

[0051] The preparation method of the self-adhesive modified paint in this embodiment is as follows: S11, by weight, 105 parts of bisphenol A type epoxy resin and 22.5 parts of phenolic epoxy resin are added to a reaction vessel, heated to 91°C and stirred to dissolve, and then 12.5 parts of carboxyl-terminated liquid nitrile rubber are added. The reaction is carried out at 107°C for 2.5 hours to obtain toughened modified epoxy resin. S12, then the toughened modified epoxy resin is cooled to 68°C, and 8 parts of dicyandiamide curing agent, 2 parts of 2-methylimidazole, 52.5 parts of mixed solvent and 6.5 parts of modified carbon nanotube agent are added and mixed evenly to obtain self-adhesive modified paint.

[0052] In this embodiment, the mixed solvent is prepared by mixing butanone and propylene glycol methyl ether acetate in a weight ratio of 1.5:1; the number average molecular weight of the terminal carboxyl liquid nitrile rubber is 4000, and the carboxyl content is 0.07 mol / kg; the epoxy equivalent of the bisphenol A type epoxy resin is 190 g / eq; and the epoxy equivalent of the phenolic epoxy resin is 170 g / eq.

[0053] The preparation method of the modified carbon nanotube agent in this embodiment is as follows: S121, carbon nanotubes were added to a mixed acid with a total weight of 6.5 times the total weight of carbon nanotubes, refluxed at 70°C for 3 hours, cooled, diluted with deionized water, filtered, washed with deionized water until pH 6.8, and dried at 90°C for 18 hours to obtain purified carbon nanotubes. S122, 3.5 parts by weight of αAl2O3, 2.5 parts by weight of sheet-like boron nitride, 1.5 parts by weight of hollow glass microspheres, 10 parts by weight of 80% ethanol solution, and 1.5 parts by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:6. Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123, 12.5 parts by weight of carbon nanotube composite were dispersed in 37.5 parts by weight of deionized water, 3.5 parts by weight of cobalt nitrate were added, stirred at room temperature for 3 hours, filtered and dried at 82°C, and then heat-treated at 175°C for 1.5 hours under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 4:1.

[0054] The self-adhesive transposition wire prepared by the method described in this embodiment is a super heat shock resistant self-adhesive transposition wire.

[0055] The carbon nanotubes in this embodiment are multi-walled carbon nanotubes with an outer diameter of 20 nm, a length of 10 μm, and a specific surface area of ​​250 m². 2 / g; the plate-like boron nitride is hexagonal boron nitride with an average particle size (D50) of 3μm and a thickness of 100nm; the average particle size (D50) of α-silicon nitride is 1μm, and the α phase content is ≥92%; the aluminum borate whiskers have a diameter of 1μm, a length of 20μm, and an aspect ratio of 15:1; the zirconium oxide is nano-zirconia with an average particle size of 50nm; the montmorillonite is sodium-based montmorillonite with a particle size of 400 mesh; the graphene is graphene oxide with 2 layers, a sheet diameter (D50) of 5μm, and an oxygen content (C / O ratio) of 2.5:1.

[0056] Comparative Example 1. Unlike Example 3, no modified montmorillonite agent was added during the preparation of the modified insulating primer.

[0057] Comparative Example 2. Unlike Example 3, in the preparation of the modified montmorillonite agent, furanized montmorillonite was directly replaced by montmorillonite raw material without the S1a and S1b steps.

[0058] Comparative Example 3. Unlike Example 3, the modified insulating primer was not treated with graphene-modifying liquid.

[0059] Comparative Example 4. Unlike Example 3, no additives were added during the preparation of the graphene modified liquid.

[0060] Comparative Example 5. Unlike Example 3, α-silicon nitride and aluminum borate whiskers were not added during the preparation of the additive.

[0061] Comparative Example 6. Unlike Example 3, zirconium oxide was not added in the preparation of the additive, and water was used instead of lanthanum chloride solution.

[0062] Comparative Example 7. Unlike Example 3, no modified carbon nanotube agent was added to the self-adhesive modified paint.

[0063] Comparative Example 8. The method for preparing the modified carbon nanotube agent differs from that in Example 3: S121, carbon nanotubes were added to a mixed acid with a total weight of 6.5 times the total weight of carbon nanotubes, refluxed at 70°C for 3 hours, cooled, diluted with deionized water, filtered, washed with deionized water until pH 6.8, and dried at 90°C for 18 hours to obtain purified carbon nanotubes. S122, 10 parts by weight of 80% ethanol solution and 1.5 parts by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:6. Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123, 12.5 parts by weight of carbon nanotube composite were dispersed in 37.5 parts by weight of deionized water, 3.5 parts by weight of cobalt nitrate were added, stirred at room temperature for 3 hours, filtered and dried at 82°C, and then heat-treated at 175°C for 1.5 hours under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is a mixture of concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 4:1. No αAl2O3, flake boron nitride, or hollow glass microspheres were added to the blend.

[0064] Comparative Example 9. Unlike Example 3, step S123 was not used in the preparation of the modified carbon nanotube agent.

[0065] Comparative Example 10 Unlike Example 3, insulation paper wrapping was not performed (i.e., step four was omitted), and the transposed wire core was used directly as the final product.

[0066] The testing standards are as follows: Coating film flexibility and thermal shock resistance (wide-side bending test): The transposed conductor samples obtained from each embodiment and comparative example were subjected to a wide-side bending test. The bending radius was "6a" of the narrow side of the conductor. After preheating in a high-temperature environment of 160℃ for 30 min, the coating film surface was checked for cracking using a 10x magnifying glass. Five samples were tested for each sample, and the number of cracked samples and the degree of cracking were recorded. Another sample was subjected to a wide-side bending test and then tested in the same way after heat aging at 180℃ for 30 min.

[0067] Self-adhesive layer bonding strength: The self-adhesive enameled flat wires obtained in each embodiment and comparative example were heated and cured at 170℃ for 20 minutes to completely cure the semi-cured self-adhesive coating. The bonding strength was tested using a universal testing machine. The bonding strength was tested at room temperature of 25℃ and high temperature of 120℃ respectively. The high temperature bonding strength retention rate was calculated as (bonding strength at 120℃ / bonding strength at 25℃ × 100%). Five samples were tested for each sample, and the arithmetic mean was taken.

[0068] Adhesion of insulating primer layer: Conduct a cross-cut test using a 1mm spacing cross-cutting tool, apply 3M tape and then peel it off, and determine the grade according to the standard (grade 0 is the best, grade 5 is the worst).

[0069] Breakdown voltage: Conduct a withstand voltage test using a continuous voltage ramp method at a ramp rate of 500V / s, and record the breakdown voltage value.

[0070] Corrosion resistance: The transposed wire samples obtained in each example and comparative example were immersed in 10% NaCl solution (salt spray corrosion), 0.1 mol / L H2SO4 solution (acidic corrosion), and 0.1 mol / L NaOH solution (alkaline corrosion) for 168 h (the corrosion solution was changed every 72 h). After being taken out, they were rinsed with deionized water and dried. The surface condition of the paint film (blistering, peeling, discoloration, etc.) was observed. The breakdown voltage retention rate after aging was tested according to the above method (breakdown voltage retention rate = breakdown voltage after corrosion / original breakdown voltage × 100%).

[0071] Weather resistance and UV aging resistance: A UVA-340 fluorescent UV lamp is used as the light source; the UV lamp has a wavelength of 340nm and an irradiance of 0.68W / m². 2 The test cycle conditions were: 8 hours of UV irradiation at 60℃, followed by 4 hours of condensation at 50℃ (without light), for a total test time of 1000 hours. After aging, the surface condition of the paint film was observed (powdering, cracking, discoloration, etc.), and the performance after aging was tested according to the following methods: Breakdown voltage retention rate: Test the breakdown voltage after aging and calculate the retention rate (breakdown voltage after aging / original breakdown voltage × 100%). Bond strength retention rate: Test the bond strength at room temperature after aging according to the above bond strength test method, and calculate the retention rate (bond strength after aging / original bond strength × 100%). Appearance evaluation: assess the levels of chalking, cracking, and discoloration.

[0072] The products of Examples 1-3 and Comparative Examples 1-10 were subjected to performance tests, and the test results are as follows: Table 1. Test results of coating film flexibility and thermal shock resistance in the examples and comparative examples:

[0073] As can be seen from Table 1, after bending at 6a and preheating at 160°C, none of the five samples in Examples 1-3 showed any cracking of the paint film. After heat aging at 180°C for 30 minutes, there was still no cracking, indicating that the modified insulating primer layer of the present invention has excellent thermal shock resistance and long-term heat aging reliability.

[0074] Severe cracking was observed in samples from Comparative Examples 1 and 3, indicating that the sheet-like barrier effect of the modified montmorillonite agent and the two-dimensional sheet-like barrier effect of the graphene-modified liquid are key to the crack resistance of the coating film. The cracking degree of Comparative Examples 2 and 4-6 was intermediate, further verifying the indispensability of each modification step. The cracking degree of Comparative Examples 7-9 was relatively mild, indicating that the self-adhesive layer has less impact on the flexibility of the coating film than the insulating primer layer, but still makes a certain contribution. In particular, the cracking of Comparative Example 9 was significantly aggravated, proving the importance of step S123 for the reinforcing effect of the carbon nanotube agent. The thermal shock resistance of Comparative Example 10 was comparable to that of the examples, indicating that the outer insulating layer mainly affects the insulation and mechanical protection rather than the flexibility of the coating film itself.

[0075] Table 2. Test results of self-adhesive layer bonding strength for each embodiment and comparative example:

[0076] As shown in Table 2, the 120℃ bond strength retention rate of Examples 1-3 was 80.6%~84.9%, while the retention rate of Comparative Examples 1-6 was only 50.0%~61.8%. This indicates that the integrity of the modified insulating primer layer has a significant impact on the high-temperature bond strength of the self-adhesive layer. Defects in the primer layer lead to a decrease in the bonding force between the primer and the self-adhesive interface at high temperatures. The retention rates of Comparative Examples 7-9 were even lower, directly proving the decisive role of the modified carbon nanotube agent in the high-temperature bond strength of the self-adhesive layer. In particular, Comparative Example 9 had the lowest retention rate among all samples, fully demonstrating the key enhancing role of the Co3O4 nano-anchor points formed by the cobalt nitrate heat treatment in step S123 in the interfacial bonding between the carbon nanotube agent and the epoxy resin matrix. The bond strength retention rate of Comparative Example 10 was close to that of the Examples, indicating that the outer insulating layer wrapping had no significant impact on the bonding performance of the self-adhesive layer itself.

[0077] Furthermore, the inventors of this invention also discovered that the bonding strength at 120°C of Comparative Examples 2-6 was lower than that of Comparative Example 1, and the bonding strength of Comparative Example 9 was lower than that of Comparative Example 7. This indicates that the modification was insufficient and there was an interface defect effect, which in turn affected the performance of the product more significantly. Only the technical solution made with the specific process and raw materials of this invention has the most significant performance effect. The technology of this invention is a multi-stage synergistic process with unique characteristics.

[0078] Table 3. Test results of adhesion and breakdown voltage of insulating primer layers in each embodiment and comparative example:

[0079] As shown in Table 3, the adhesion of Examples 1-3 was all grade 0, and the breakdown voltage was 11.2~13.8kV, which was much better than that of Comparative Examples 1-6. The breakdown voltage of Comparative Example 3 was only 8.0kV, indicating that the graphene modified liquid contributed the most to improving the density and voltage resistance of the insulation layer. The adhesion of Comparative Examples 7-9 was still grade 0, and the breakdown voltage was 10.2~11.0kV, which was better than that of Comparative Examples 1-6 but lower than that of Example 3, indicating that the modification state of the carbon nanotube agent in the self-adhesive layer also had a certain impact on the overall insulation performance. The breakdown voltage of Comparative Example 10 was comparable to that of Example 3, indicating that the outer insulation layer had little impact on the bulk breakdown voltage of the conductor insulation layer, but its main function was to provide additional insulation protection and mechanical protection.

[0080] Table 4. Paint film condition and breakdown voltage retention rate of each embodiment and comparative example after immersion in different corrosive media for 168 hours:

[0081] As shown in Table 4, after immersion in three corrosive media for 168 hours, the paint films in Examples 1-3 showed no blistering or peeling, only slight discoloration in acidic and alkaline media, with a breakdown voltage retention rate of 88.4%~95.7%. The corrosion resistance of Comparative Examples 1-6 deteriorated significantly, especially Comparative Example 3, whose breakdown voltage retention rate was only 63.8%~70.0%, indicating that the two-dimensional barrier effect of the graphene-modified liquid is the core of its anti-corrosion performance. The corrosion resistance of Comparative Examples 7-9 was better than that of Comparative Examples 1-6 but worse than that of Examples 1-6, with Comparative Example 9 having the lowest breakdown voltage retention rate, indicating that step S123 also makes an important contribution to the stable dispersion and corrosion resistance of the carbon nanotube agent in the self-adhesive layer. The corrosion resistance of Comparative Example 10 was basically equivalent to that of Example 3, indicating that the contribution of the outer insulation layer wrapping to the corrosion resistance of the conductor body is mainly reflected in physical isolation protection rather than chemical corrosion prevention.

[0082] Table 5. Performance test results of each embodiment and comparative example after 1000h UV aging:

[0083] As shown in Table 5, after 1000 hours of UV aging, the paint films of Examples 1-3 showed no significant changes, with chalking and cracking grades both at level 0, breakdown voltage retention rate at 87.5%~91.3%, and bond strength retention rate at 80.2%~84.1%, demonstrating excellent UV aging resistance. The performance of Comparative Examples 1 and 2 after UV aging was also significantly worse than that of the Example, with both chalking and cracking grades at level 1 and breakdown voltage retention rates of only 72.1% to 73.9%. The modified montmorillonite agent's lamellar structure not only has a barrier effect, but the trace metal ions contained in its interlayers also have UV absorption function. After sulfuric acid activation and furanization modification, the interlayer spacing of montmorillonite increased, and the UV absorption capacity was further enhanced. Without this component, the UV resistance of the paint film decreased significantly. Comparative Example 3 showed the most severe performance degradation after UV aging, exhibiting significant loss of gloss, discoloration, and slight powdering. The breakdown voltage retention rate was only 65.2%, and the bond strength retention rate was only 58.6%. This is because the two-dimensional sheet structure of graphene has an excellent UV shielding effect, which can effectively absorb and scatter UV light, protecting the resin matrix from photo-oxidative degradation. At the same time, the oxygen-containing functional groups on the surface of graphene can form chemical bonds with the resin matrix, enhancing interfacial stability. Without the graphene modification solution, the insulating primer layer is directly exposed to UV irradiation, and the polymer chains break down and degrade rapidly. The lack of internal components in the graphene-modified liquids in Comparative Examples 4-6 also led to a decline in UV aging performance, indicating that the UV protection function of each component in the additive is irreplaceable and synergistic, and the lack of any one component will lead to a significant deterioration in overall performance. Comparative Examples 7 and 8 showed better performance after UV aging than Comparative Examples 1-6 but worse performance than the Example, with a breakdown voltage retention rate of 84.3%~85.1%. This indicates that the modified carbon nanotube agent contributes to UV resistance but is not the decisive factor. Comparative Example 9 showed loss of gloss, discoloration, and cracking after UV aging, with a breakdown voltage retention rate of only 79.6%. The untreated carbon nanotubes lacked Co3O4 nano-anchoring points on their surface, resulting in insufficient interfacial bonding and loss of UV shielding function, leading to a decline in performance after UV aging. Comparative Example 10 showed significant discoloration and chalking after UV aging, with a breakdown voltage retention rate of only 78.2%. This indicates that the outer insulation layer of the insulating paper is not only a mechanical protective layer but also the first barrier against UV radiation. The outer insulation layer directly faces UV radiation, absorbing and scattering most of the UV light, effectively protecting the internal insulating primer layer and self-adhesive layer.

[0084] In summary, this invention, through its self-made modified insulating primer, self-adhesive modified varnish, and insulating paper outer insulation layer, provides a triple protection system that enables transposed conductors to maintain excellent insulation performance and bonding strength even after 1000 hours of accelerated UV aging. The breakdown voltage retention rate is ≥87.5%, and the bonding strength retention rate is ≥80.2%, which is far superior to the comparative examples. The preparation steps of each functional component of this invention are indispensable and together constitute a complete weather-resistant and UV-resistant protection system.

[0085] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0086] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing ultra-thermal shock resistant self-adhesive transposition conductors, characterized in that, Includes the following steps: Step 1: Clean and dry the copper flat wire conductor, then coat it with a modified insulating primer, and then bake and cure it to obtain a primer layer with a thickness of 0.1~0.12mm; Step two, then apply a self-adhesive modified paint to the outside of the primer layer, and then cure to form a self-adhesive layer with a thickness of 0.04~0.06mm; Step 3: Arrange 19 to 37 copper flat wires made in Step 2 into two columns with their wide sides in contact with each other. Then, transpose the two columns of self-adhesive enameled flat wires in the same direction along their narrow sides to obtain transposed wire cores. Step four: Wrap the transposed core with 5 to 7 layers of continuous and tight insulating paper to obtain an ultra-heat-shock resistant self-adhesive transposed conductor.

2. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 1, characterized in that, The baking and curing process described in step one is carried out using a vertical enameling oven. The temperature of the inlet section of the vertical enameling oven is controlled at 120~140℃, the temperature of the lower section at 220~250℃, the temperature of the middle section at 300~350℃, and the temperature of the upper section at 350~400℃. The oven speed is 8~12m / min. In step two, the curing process is carried out using a vertical enameling oven. The inlet temperature of the vertical enameling oven is controlled as follows: inlet temperature 120~150℃, lower temperature 160~200℃, middle temperature 280~310℃, upper temperature 320~350℃, and oven speed 8~12m / min.

3. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 1, characterized in that, The modified insulating primer is prepared by: S1, by weight, heat 100-110 parts of acetal resin to 100-105℃, keep warm, and set aside. Then add 8-12 parts of modified montmorillonite agent and 1-3 parts of silane coupling agent KH560 to 30-50 parts of ethanol solvent and mix thoroughly to obtain the additive. S2, add the additive to the prepared acetal resin and stir for 2-4 hours, then cool to 80-85℃, add 8-12 parts of curing agent, stir evenly to obtain modified insulating primer.

4. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 3, characterized in that, The curing agent is a blocked isocyanate curing agent, and the blocked isocyanate curing agent is an imidazole blocked isocyanate.

5. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 3, characterized in that, The modified montmorillonite agent is prepared by: S1a, montmorillonite is first stirred evenly in a sulfuric acid solution with a mass fraction of 5-8% at 10-15 times the total weight of montmorillonite, then washed with water, filtered, and dried to obtain dry montmorillonite; S1b: 5-8 parts by weight of montmorillonite are dispersed in 15-20 parts by weight of N,N-dimethylformamide, and 2-3 parts by weight of furanylmethyl glycidyl ether are added. The mixture is reacted at 60-65°C for 5-8 hours. After the reaction is completed, the mixture is washed with water, filtered, and dried to obtain furanylated montmorillonite. S1c, furanized montmorillonite and graphene modified liquid were stirred at a weight ratio of 3:(5~7) for 1~2 hours at a stirring speed of 450~550 r / min and a stirring temperature of 55~60℃. After stirring, the mixture was filtered and dried to obtain the modified montmorillonite agent.

6. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 5, characterized in that, The preparation method of the graphene-modified liquid is as follows: S1c1, mix 2-3 parts by weight of silane coupling agent KH550 and 30-35 parts by weight of 80-85% ethanol solution, then adjust the pH to 4.5-5.0 with acetic acid, then add 4-7 parts by weight of additive, and continue to stir evenly to obtain the modified solution. The preparation method of the additive is as follows: 2-4 parts by weight of α-silicon nitride, 1-3 parts by weight of aluminum borate whiskers, 5-8 parts by weight of 2-5% lanthanum chloride solution, and 2-3 parts by weight of zirconium oxide are blended and ball-milled thoroughly. After ball milling, the mixture is filtered and dried to obtain the additive. S1c2, graphene and the modified liquid are ultrasonically modified at a weight ratio of 5:(8~11), ultrasonic power 350~450W, ultrasonic for 1~2h, and after ultrasonication is completed, graphene modified liquid is obtained.

7. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 1, characterized in that, The preparation method of the self-adhesive modified paint is as follows: S11, by weight, 100-110 parts of bisphenol A type epoxy resin and 20-25 parts of phenolic epoxy resin are added to a reaction vessel, heated to 90-92℃ and stirred to dissolve, and then 10-15 parts of carboxyl-terminated liquid nitrile rubber are added, and reacted at 105-110℃ for 2-3 hours to obtain toughened modified epoxy resin. S12, then the toughened modified epoxy resin is cooled to 65~70℃, and 7~9 parts of dicyandiamide curing agent, 1~3 parts of 2-methylimidazole, 50~55 parts of mixed solvent and 5~8 parts of modified carbon nanotube agent are added and mixed evenly to obtain self-adhesive modified paint.

8. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 7, characterized in that, The mixed solvent is prepared by mixing butanone and propylene glycol methyl ether acetate in a weight ratio of (1~2):1; the number average molecular weight of the terminal carboxyl liquid nitrile rubber is 3000~5000, and the carboxyl content is 0.05~0.10 mol / kg; the epoxy equivalent of the bisphenol A type epoxy resin is 180~200 g / eq; and the epoxy equivalent of the phenolic epoxy resin is 160~180 g / eq.

9. The method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to claim 7, characterized in that, The modified carbon nanotube agent is prepared by: S121, add carbon nanotubes to a mixed acid with a weight of 5 to 8 times the total weight of carbon nanotubes, reflux at 60 to 80°C for 2 to 4 hours, cool, dilute with deionized water, filter, wash with deionized water until pH is 6.5 to 7.0, and dry at 80 to 100°C for 12 to 24 hours to obtain purified carbon nanotubes. S122, 2-5 parts by weight of αAl2O3, 2-3 parts by weight of sheet-like boron nitride, 1-2 parts by weight of hollow glass microspheres, 8-12 parts by weight of 75-85% ethanol solution, and 1-2 parts by weight of silane coupling agent KH550 are mixed evenly to obtain a blend. The purified carbon nanotubes and the blend are mixed thoroughly at a weight ratio of 3:(5-7). Then, the mixture is filtered and dried to obtain a carbon nanotube composite. S123: 10-15 parts by weight of carbon nanotube composite are dispersed in 35-40 parts by weight of deionized water, 2-5 parts by weight of cobalt nitrate are added, the mixture is stirred at room temperature for 2-4 hours, filtered, dried at 80-85℃, and then heat-treated at 150-200℃ for 1-2 hours under nitrogen atmosphere to obtain modified carbon nanotube agent. The mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a weight ratio of (3~5):

1.

10. The self-adhesive transposition conductor prepared by the method for preparing the ultra-thermal shock resistant self-adhesive transposition conductor according to any one of claims 1 to 9.